Analisis Tingkat Kualitas Pelayanan terhadap Kepuasan Pasien Pemegang Kartu Jamkesmas di Puskesmas Sukaraja Kabupaten Lombok Timur - Muhamad Zaril Gapari (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
This study aims to analyze the level of service quality on patient satisfaction of Jamkesmas card holders at Sukaraja Health Center, East Lombok Regency. This type of research is descriptive, the purpose of which is to describe the variables that influence patient satisfaction of Jamkesmas card holders at Sukaraja Health Center and the sampling technique uses Incidental Sampling, by taking a sample of 100 respondents who are patients who seek treatment using Jamkesmas cards at Sukaraja Health Center. Data collection techniques use questionnaires and documentation. Data analysis used in this study is simple linear regression analysis, and testing the hypothesis using the t-test (t-test). The results of the analysis obtained service quality variables that include (tangible, reliability, responsiveness, assurance, and empathy) of 30.8%, meaning that the dependent variable (patient satisfaction) can be explained by the independent variable (service quality: tangible, reliability, responsiveness, assurance, and empathy) while the remaining 60.2% can be explained by other variables. Meanwhile, the t-test (partially) shows that the service quality variables tangible, reliability, responsiveness, assurance, and empathy have a significant effect on customer satisfaction. This is proven by the significance level of each variable being 0.000 < 0.10.